DEVELOPMENT OF YOUTH’S ENTREPRENEURIAL COMPETENCE AS A SOCIO-PSYCHOLOGICAL PROBLEM - Lavrenko , Olha (PSYCHOLOGICAL JOURNAL, 2025)
The article explores the essence of entrepreneurial competence among youth as a socio-psychological issue. Entrepreneurial competence is defined as the process of developing an individual’s ability to initiate, plan, organize, and implement entrepreneurial activities. It encompasses not only knowledge and skills but also specific psychological qualities and attitudes toward entrepreneurship. Attention is drawn to the distinction between the concepts of "competence" and "competency." The article highlights how the concept of "entrepreneurial competence" is interpreted by domestic scholars, both in a broad and narrow sense. It is noted that the structure and components of entrepreneurial competence remain a subject of scientific debate. According to J. Raven, the components of competence as a personal construct include: cognitive (knowledge, skills, abilities), affective (orientation, emotions, motivation, values, attitudes), volitional (behavioral effort, energy mobilization, persistence), and experiential elements (problem-solving, cooperation, success, and satisfaction from completed tasks). A generalized perspective of scholars on the components of entrepreneurial competence is presented. The article emphasizes that the development of entrepreneurial competence is essential not only for personal growth but also for social development and the economic progress of the country. The essence of the concepts "entrepreneurial competence" and "key competence" is clarified. A core set of competencies is necessary for personal development, social integration, active citizenship, and employment, as well as for expanding opportunities in the labor market. These competencies are developed through lifelong learning, starting from early childhood via formal, non-formal, and informal education. It is noted that the development of entrepreneurial competence occurs gradually—beginning in school education and continuing through institutions of higher and vocational education. Acquiring entrepreneurial competence requires a transition from convergent thinking (narrowing possibilities to find one correct answer) to divergent thinking (developing mental abilities related to creativity, innovation, imagination, and resourcefulness). The essence of the EntreComp (Entrepreneurship Competence Framework) is discussed as a tool for enhancing the entrepreneurial potential of individuals and organizations across Europe. The importance of incorporating the experience of European countries into domestic educational practice—by adopting EU principles, approaches, tools, and methods in the development of entrepreneurial competence among youth—is emphasized.